1973
DOI: 10.1007/bf01230690
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural morphometry of the pancreatic ?-cell

Abstract: Summary. Standard stereological methods have been used to determine the morphometric parameters of organelles contained in the fi-eells of mouse pancreas. Sectioned material from ten islets was analysed at three levels of magnification in the electron microscope. Quantitative data was obtained about the volume number and surface area of the various cytological components and was expressed as density per cm a of tissue and as absolute dimensions for the average fl-eell. The organelles studied were the nucleus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
178
1
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(202 citation statements)
references
References 12 publications
22
178
1
1
Order By: Relevance
“…The average number of LDCVs in MIN6 cells was 2,412 Ϯ 563 granules per cell. This is in close agreement with measurements of the average diameter (311 Ϯ 45 nm) and number (3,290 granules per MIN6 cell) of immunostained insulin granules and values reported in other studies (2)(3)(4).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The average number of LDCVs in MIN6 cells was 2,412 Ϯ 563 granules per cell. This is in close agreement with measurements of the average diameter (311 Ϯ 45 nm) and number (3,290 granules per MIN6 cell) of immunostained insulin granules and values reported in other studies (2)(3)(4).…”
Section: Resultssupporting
confidence: 80%
“…Roughly 1,000 granules are morphologically docked to the plasma membranes, and perhaps 100 of these are in a readily releasable pool. Only a small proportion of total insulin is released even under maximal stimulatory conditions (4,5). Mechanisms that control transfer of granules to the readily releasable pool as well as details of release activation remain unresolved.…”
mentioning
confidence: 99%
“…This is not much different from the pool size deduced from the transient stimulation of exocytosis elicited by cAMP at 60 nÒ [Ca¥]é (80 granules). Collectively, these results suggest that in the pancreatic B-cell the readily releasable pool under control conditions is of very limited size and contains û0·5% of the total number of granules within the cell (13100 granules; Dean, 1973). The fact that exocytosis continues for much longer in the infusion experiments when cAMP is present ( Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, although there are no data to rule out that secretion of DCVs normally occurs from wild-type motor neuron somas, the reconstruction data suggest that motor neurons do not use somas to store a large reservoir of DCVs for secretion. This contrasts with neuroendocrine cells, such as chromaffin cells and pancreatic b-cells, in which DCVs number in the tens of thousands per cell and can occupy 31 and 12% of the cell soma volume, respectively (Dean 1973;Plattner et al 1997).Abnormal neuropeptide function contributes to the sluggish locomotion of unc-43 lf mutantsIf unc-43 mutants secrete native neuropeptides abnormally from their motor neuron somas instead of their axons, this could affect the animal's locomotion behavior. Similarly, the 90% reduction in axonal DCVs in motor neurons could also affect the animal's locomotion behavior.…”
mentioning
confidence: 87%
“…The DCVs in neuroendocrine and PC12 cells are much more abundant and accessible to biochemical and physiological experiments than those in neurons. For example, in chromaffin and pancreatic b-cells (both neuroendocrine cells), DCVs can number in the tens of thousands per cell and can occupy 31 and 12% of the cell volume, respectively (Dean 1973;Plattner et al 1997). Exploiting these advantages, studies in PC12 and neuroendocrine cells have revealed that DCVs arise from a regulated secretory pathway.…”
mentioning
confidence: 99%